2008
DOI: 10.1080/01674820801970306
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome in Thai Nurses

Abstract: According to the Thai PSST, 25.1% of Thai nurses are suffering from PMS. The significant associated factors were more coffee consumption and negative attitude toward menstruation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
4
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 26 publications
6
33
4
8
Order By: Relevance
“…[4,5,6,7] In the study by Polat et al, [7] the prevalence of dysmenorrhea was 72.7%. 66.2% suffered from severe and moderate dysmenorrhea which was similar to the study by Burnett et al [4] In the study conducted on 432 nurses by Chaya Chinda C et al, [8] the prevalence of dysmenorrhea was 25.1%. In Tang Chaik et al [9] study, the prevalence of dysmenorrhoea was 84.2%, 4.7% had severe dysmenorrhea.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[4,5,6,7] In the study by Polat et al, [7] the prevalence of dysmenorrhea was 72.7%. 66.2% suffered from severe and moderate dysmenorrhea which was similar to the study by Burnett et al [4] In the study conducted on 432 nurses by Chaya Chinda C et al, [8] the prevalence of dysmenorrhea was 25.1%. In Tang Chaik et al [9] study, the prevalence of dysmenorrhoea was 84.2%, 4.7% had severe dysmenorrhea.…”
Section: Discussionsupporting
confidence: 75%
“…Long and heavy menstrual flow was associated with severity of pain. Chaya Chinda C et al [8] observed that younger age, nulligravida, lower income, coffee consumption of greater than 1 cup/day, complained of moderate-to-severe dysmenorrhea and had negative attitude towards menstruation. Di Cintio E et al [17] analysed 106 women with moderate and severe dysmenorrhea observed that women with irregular, long, heavy menstrual flow had dysmenorrhea and there was no distribution with dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…But this statistic is lower than the results of the study of Alavi et al, which had been done among the students of Bandar Abbas University of Medical Sciences University. Also, this statistic is significantly higher than the results of the study of Asiabar et al, (Kiani et al, 2009) and the studies done in Thailand and Japan (Chayachinda et al, 2008;Takeda et al, 2006). These data indicated that is spite of numerous questionnaires (retrospective and prospective), the prevalence of premenstrual syndrome in Iran is almost similar and higher than the extent observed from the other countries.…”
Section: Discussioncontrasting
confidence: 56%
“…But in the study of Chayachinda, the most symptoms of the PMS were irritability, overeating and oversleeping or insomnia (Chayachinda et al, 2008). Also in the study of Smith, eating has been reported as the most common symptom of the premenstrual syndrome (Cleckner-Smith et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the PSST identifies women who would benefit from a more in-depth diagnostic interview for the diagnosis of PMDD, without the need to monitor symptoms over two reproductive cycles. 16 The PSST has been translated into and/or validated in several languages, including Spanish, 20 Persian, 21 German, 22,23 Thai, 24 Chinese, 25 and Finish. 26 In the present study, we set out to develop and validate a Brazilian Portuguese version of this instrument, including content validity, internal consistency, and test-retest reliability.…”
mentioning
confidence: 99%